Air‐stable zirconium (IV)‐salophen perfluorooctanesulfonate as a highly efficient and reusable catalyst for the synthesis of 3, 4‐dihydropyrimidin‐2‐(1H)‐ones/thiones under solvent‐free conditions. (30th December 2019) - Li, Ningbo; Wang, Yijun; Liu, Feijun; Zhao, Xin; Xu, Xinhua; An, Quan; Yun, Keming
Abstract : An air‐stable complex of zirconium (IV)‐salophen perfluorooctanesulfonate (1 ) was successfully synthesized by reacting Zr (salphen)Cl2 and C8 F17 SO3 Ag. Complex 1 was characterized and studied by different techniques (NMR, IR, HRMS, TG‐DSC, conductivity and acidity measurements), and was found to be air‐stable, water tolerant, thermally stable and strongly Lewis‐acidic. Complex 1 exhibited high catalytic efficiency for the synthesis of 3, 4‐dihydropyrimidin‐2‐(1H)‐ones/thiones via the Biginelli reaction of aldehydes, 1, 3‐dicarbonyl compounds and urea/thiourea under solvent‐free conditions. Furthermore, complex 1 could be reused 5 times with minimal changes in catalytic efficiency. Compared with previously reported methods, the important features of this protocol are the solvent‐free conditions, the short reaction times, the wide substrate compatibility, the high efficiency and the good reusability. Abstract : An air‐stable zirconium (IV)‐salophen perfluorooctanesulfonate complex was successfully synthesized, and showed high catalytic activity for the synthesis of 3, 4‐dihydropyrimidin‐2‐(1H)‐ones/thiones via Biginelli reaction of aldehydes, 1, 3‐dicarbonyl compounds and urea/thiourea. Compared to the reported methods, the main advantage of this protocol is (i) solvent‐free conditions, (ii) short reaction time, (iii) high efficiency, (iv) wide substrate scope and (v) good reusability.